ʺThe Moodle database and its application in the learning processʺ - Litvinov, A.; Gavrilenko, I. (Problems of Engineer-Pedagogical Education, 2022)
The paper presents the results of using the “Database” element in the Moodle learning management system for computer disciplines in relation to distance education. An analysis of applying the Moodle system in education was carried out, whose findings allow claiming that most of the publications are descriptive in nature, often repeating the technical manuals of the Moodle user site and rarely taking into account the peculiarities of specific branches of knowledge. In the course “Fundamentals of Scientific Research” several students can be given complex computational and graphic work on the development of a new model of equipment. This implies joint work to form a list of project analogues. In fact, this is a patent search and the Moodle Database element is ideal for a few students. As a part of a Moodle course, this structure is a data table. At the same time, the format and structure of the records are practically limitless. These can be images, files, hyperlinks, text, and more. At the physical level, the Moodle database consists of records, each of which describes the attributes of a particular object, such as a description of a device in a patent search. A record consists of fields of different types, each of which describes one attribute of an object, while all the records of one database have the same set of fields. The types of fields and their features are considered. A rather exotic type of field is described in detail – “Latitude/Longitude”, which allows entering the coordinates of a point or object on the globe, and then use geographic services for viewing. As a database interface, so-called templates are used, which allow customizing the forms for viewing records and forms for entering and editing records. Database templates are built on the same principles and are HTML pages with a corresponding set of tags that are interpreted by the browser. There are two types of tags: information and control. They can be configured either in the built-in WYSIWYG or HTML editors. A template for displaying database records as a list is proposed, which is more informative than the built-in template. The technology of development of the Moodle “Database” element, which consists of several interrelated stages, is offered. The process of creating the Moodle “Database” element is demonstrated with an example of the results formation for a collective patent search on the topic “Priority Devices” in the course “Fundamentals of Scientific Research” for computer disciplines.